Ethiopian honeybee propolis: a novel natural source for the green synthesis of silver nanoparticles with enhanced biological activities - Waktole, Gemechis; Chala, Bayissa; Belay, Abebe; Teshome, Lemma (Frontiers in Nanotechnology, 2025)
Propolis, a natural resinous substance produced by honeybees (Apis mellifera L.), is a complex mixture of over 300 bioactive compounds with significant pharmaceutical potential. In light of the escalating global antimicrobial resistance crisis, there is an urgent need for novel antimicrobial agents. This study aimed to synthesize and characterize silver nanoparticles (AgNPs) using Ethiopian propolis and evaluate their antimicrobial and antioxidant properties. The synthesis of propolis-mediated silver nanoparticles (Pro-AgNPs) was optimized and characterized using UV-visible spectrophotometry, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD). The UV-Vis spectra revealed a maximum absorbance at 424 nm, confirming the successful synthesis of AgNPs. FT-IR analysis identified functional groups involved in nanoparticle stabilization, while XRD confirmed the crystalline nature of the nanoparticles. SEM images revealed spherical-shaped nanoparticles with uniform size distribution. The antimicrobial activity of Pro-AgNPs was evaluated against Gram-negative Pseudomonas aeruginosa (ATCC 27853) and Gram-positive Enterococcus faecalis (ATCC 29212) bacteria, demonstrating significant growth inhibition zones of 15.67 ± 0.57 mm and 17.33 ± 1.15 mm, respectively, at a concentration of 50 μg/mL. The antioxidant activity of Pro-AgNPs and propolis extract was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, revealing concentration-dependent radical scavenging activity. Pro-AgNPs exhibited potent antioxidant activity, with an IC50 value of 45.54 ± 0.57 μg/mL. These findings underscore the potential of Pro-AgNPs as natural antimicrobials and antioxidants, with promising applications in pharmaceuticals, cosmetics, and the food industry.